Lepyrodiclis alinihatii (Caryophyllaceae), a new species from Turkey. (17th March 2021) - Menemen, Yusuf; Yalçınkaya, Ramazan; Erden, Ayşe
Abstract : A new species, Lepyrodiclis alinihatii, is described from the eastern Anatolia region of Turkey. Diagnostic and morphological characteristics that distinguished it from its allied species, L. holosteoides, and an identification key for all Lepyrodiclis species are provided. Lepyrodiclis alinihatii differs from L. holosteoides by its paniculate inflorescence, rarely with terminal cymes, glabrous pedicels, ovate or ovate‐oblong and glabrous sepals with broad scarious margin, large obovate to subcircular, deeply notched petals, turbinate ovary and thick (not thin) stilus. Moreover, L. alinihatii pollen grains differ from those of L. holosteoides by their pore number: 18–20, pore diameter: 3.56–5.00 µm, interporal distance: 6.0–6.5 µm, and number of microechini per sample area of 5 × 5 µm: 15–20.